Effects of Age‐Related Aortic Root Anatomic Changes on Left Ventricular Outflow Tract Pace‐Mapping Morphologies: A Cardiac Magnetic Resonance Imaging Validation Study. (8th July 2015) - MAEDA, SHINGO; CHIK, WILLIAM W.; HAN, YUCHI; LIANG, JACKSON J.; SQUARA, FABIEN; ARKLES, JEFFREY S.; SADEK, MOUHANNAD M.; SANTANGELI, PASQUALE; FRANKEL, DAVID S.; ZADO, ERICA S.; TAKEBAYASHI, SATOSHI; DIXIT, SANJAY; et al.
Age‐Related Changes in the Left Outflow Tract Introduction Outflow tract ventricular arrhythmias (OT VAs) are common and catheter ablation is an effective treatment option. We sought to investigate the relationship between age‐related anatomic aortic root changes and QRS morphology during left ventricular outflow tract (LVOT) pace‐mapping using cardiac magnetic resonance (CMR) imaging. Methods and Results Fifty‐one patients undergoing CMR imaging were divided into 3 groups based on age (<40, 40–60, >60 years). We measured the angle of the aortic root, the aorta to ventricular septal angle, the distance between the right coronary cusp (RCC) and left coronary cusp (LCC), and the distance between the ascending and descending aorta. Additionally, we evaluated the QRS morphologies obtained during pace‐mapping from the LVOT. In older patients, LCC was more superior to the RCC (P < 0.01). Age was positively correlated with the aortic root angle (r2 = 0.481, P < 0.01) as well as the distances between the ascending and descending aorta at a level below the arch (r2 = 0.569, P < 0.01). In older patients, LVOT pace‐mapping (performed in 16 patients) demonstrated higher maximal R‐wave amplitude, and was greater when pacing from the LCC versus the RCC in lead III (1.8 ± 0.7 vs. 1.0 ± 0.5 mV, P = 0.02). Conclusion The anatomy of the aortic root changes with age, and age‐related aortic root changes may affect the QRS morphology during pace‐mapping. Understanding the potential anatomic changes that accompany aging is important to maximize the efficacy of catheter ablation of OT VAs.